Comparison analysis of chattering in smooth sliding mode controlled DC-DC buck converter using constant plus proportional reaching law and proposed reaching laws - K. B. Siddesh; B. Banakara; R. Shivarudraswamy (Institute of Advanced Engineering and Science, 2020)
This paper presents a comparative analysis of chattering in sliding mode controlled DC-DC buck converter for chattering suppression using constant plus proportional reaching law and proposed reaching laws. A smooth SMC is used for chattering suppression in buck converter. The different switching functions are used in proposed reaching laws and constant plus proportional reaching law applied to SMC buck converter, the tan hyperbolic reaching law, sigmoid reaching law and constant plus proportional rate reaching law. The proposed method tan hyperbolic gives less switching loss among the reaching laws and stable output voltage. Inturn, performance of the buck converter increases, tanhyperbolic reaching law is more sensitive to matched, mismatched disturbance and parameter uncertainties. Loading conditions are also applied to the buck converter to measure the disturbances and parametric variations. The results are verified by MATLAB/Simulink.